PEMBERDAYAAN PEREMPUAN BERBASIS MASJID MELALUI PROGRAM LUMBUNG PADI DI DESA GENENG, JAMBAKAN, BAYAT, KLATEN, JAWA TENGAH - Hamsah, Ustadi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2017)
A discourse of women empowerment has been understood to be based on social capital , from the existence and the role of women themselves. This article is an attempt to enrich the discourse of women empowerment based on mosque. The function and the role of mosque will be socially linked to the patterns of womenâ€™s empowerment in creating food security i.e. rice barns. So far, the function of mosque is seen limited to a place for religious rituals that have a limited implication on its social role. Similarly, the function and the role of women in the village in particular, are also limited in the public sector. By using the constructive theory of Peter L. Berger, the analysis argues that the â€œcultureâ€ of the mosque provides an affinity for village women to develop empowerment models in the form of rice granaries with the patterns of participation and local organizational capacity. Supported by theological values of the mosqueâ€™s function and role, both patterns allow women to play their social functions and roles to be more wider.[Wacana pemberdayaan perempuan yang selama ini dipahami merupakan wacana yang berbasis social capital dari eksistensi dan peran perempuan itu sendiri. Artikel ini merupakan upaya untuk memperkaya wacana men- genai pemberdayaan perempuan yang berbasis masjid. Fungsi dan peran masjid secara sosial akan dikaitkan de- ngan pola-pola pemberdayaan perempuan dalam menciptakan ketahanan pangan yakni lumbung padi. Hal yang menarik adalah wacana bahwa masjid difungsikan sebatas pada tempat ritual keagamaan yang berimplikasi pada peran sosialnya yang sangat terbatas. Kemudian perempuan di desa, khususnya, juga dilihat fungsi dan perannya secara terbatas di sektor publik. Analisis dari persoalan ini dilakukan dengan menggunakan teori teori konstruk- sionisme Peter L. Berger. Dari analisis itu dapat dikemukakan bahwa â€œcultureâ€ masjid memberikan afinitas bagi perempuan desa untuk mengembangkan model pemberdayaan dalam bentuk lumbung padi dalam dengan pola par- ticipation dan local organizational capacity. Kedua pola itu memungkinkan perempuan memainkan fungsi dan peran sosialnya yang lebih luas dan didukung oleh values teologis dari fungsi dan peran masjid.]